Intraoperative fetal monitoring: The fetus as a target organ - Navarro-Vargas, José Ricardo; Romero Fuentes, Sandra Milena (Colombian Journal of Anesthesiology, 2014)
Introduction: A reflection based on the article “The blind spot of obstetric anesthesia: intraoperative fetal monitoring” is made, with examples of non invasive monitoring developed in other fields, and a discussion about the expectation of a new device that could prove to be useful for intra-surgical fetal monitoring. Methods: Reading the above-mentioned article, manual search of information about new non-invasive monitoring devices currently being developed that are applicable to diverse situations and patients, and may open up new avenues for intraoperative fetal monitoring in the future. Results: Description of examples of non-invasive monitoring tools that have been developed in the last few years as a result of the need to obtain reliable and real-time information about target organ behavior during the perioperative period. Conclusion: A practical and reliable intraoperative fetal monitoring device is not yet available for obstetric patients in the OR. We suggest the implementation of a novel device similar to those available for the detection of arrhythmias, as a potential tool for non-invasive intraoperative fetal monitoring.